2020
DOI: 10.1101/2020.06.29.171512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional solubilisation of the β2-adrenoceptor (β2AR) using Diisobutylene maleic acid (DIBMA)

Abstract: AbstractThe β2-adrenoceptor (β2AR) is a well-established target in asthma and a prototypical GPCR for biophysical studies. Solubilisation of membrane proteins has classically involved the use of detergents. However, the detergent environment differs from the native membrane environment and often destabilises membrane proteins. Use of amphiphilic copolymers is a promising strategy to solubilise membrane proteins within their native lipid environment in the complete absence of de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…DIBMA has recently been used to solubilise the β 2 AR from HEK293 membranes. Whilst the material was not purified, detailed analysis of the stability and activity of the receptor in the resulting nanoparticles showed that receptor ligand binding affinity was similar in DIBMA nanoparticles, membranes and detergent, whilst receptor thermostability was improved by 10°in DIBMA nanoparticles versus detergent (Harwood et al 2020). We have shown that a polymethacrylate (PMA) co-polymer can be used to solubilise NTSR1 from Sf9 membranes (Lavington and Watts 2021).…”
Section: Polymer Lipid Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…DIBMA has recently been used to solubilise the β 2 AR from HEK293 membranes. Whilst the material was not purified, detailed analysis of the stability and activity of the receptor in the resulting nanoparticles showed that receptor ligand binding affinity was similar in DIBMA nanoparticles, membranes and detergent, whilst receptor thermostability was improved by 10°in DIBMA nanoparticles versus detergent (Harwood et al 2020). We have shown that a polymethacrylate (PMA) co-polymer can be used to solubilise NTSR1 from Sf9 membranes (Lavington and Watts 2021).…”
Section: Polymer Lipid Nanoparticlesmentioning
confidence: 99%
“…However, in spite of these limitations, it is clear that SMA can work well for GPCRs, and so it will be pertinent to test in most cases. In cases where SMA is less appropriate, the development of (Hall et al 2018) β 2 AR DIBMA HEK293 No purification (Harwood et al 2020) alternative polymers has circumvented most of the practical issues of SMA. DIBMA and SMI can both solubilise GPCRs with retention of function into nanoparticles less sensitive to the presence of divalent cations, whilst PMA can solubilise and purify functional NTSR1 in the presence of divalent cations.…”
Section: Polymer Lipid Nanoparticlesmentioning
confidence: 99%
“…The related DIBMA copolymer has been used to solubilize the β2-adrenoceptor (β2AR), which is sensitive to phospholipid composition [ 51 ]. Comparison of binding activities of β2AR in membrane or DIBMA-based nanodiscs reveals comparable interactions with full agonist (isoprenaline), antagonist (propranolol) and inverse agonist (ICI 118,551), while DDM detergent significantly destabilizes the protein [ 52 ]. Given such options, synthetic copolymer kits have been developed by Cube Biotech and Orbiscope for comparing the performance of various copolymers when purifying active target proteins.…”
Section: Native Gpcr–lipid Complexesmentioning
confidence: 99%
“…SMA creates stable nanoparticles 10-11nm in diameter, containing an MP in a lipid bilayer that is suitable for downstream structural and biochemical studies [109,[131][132][133]. SMALPs have been used to successfully encapsulate transporters, ion channels, enzymes, receptors and large complexes [131,[134][135][136][137][138][139][140][141]. A drawback of SMA is that it is pH sensitive and has a high negative charge.…”
Section: Use Of Encapsulation Agents To Stabilise Membrane Proteinsmentioning
confidence: 99%
“…DIBMALPs can tolerate low millimolar concentrations of divalent cations accelerating solubilisation by several fold, which helps in functional biophysical assays [145][146][147]. SMA-PAGE combines the MP encapsulation of SMALPs with native gel electrophoresis to separate MP complexes along with surrounding phospholipids in their native state [137,148]. MP-SMALPs can be extracted from gel bands and analysed using EM and mass spectrometry.…”
Section: Use Of Encapsulation Agents To Stabilise Membrane Proteinsmentioning
confidence: 99%